PENERAPAN RANGE OF MOTION (ROM) KOMBINASI HEAD OF BED PADA PASIEN STROKE ISKEMIK DENGAN MASALAH KEPERAWATAN GANGGUAN MOBILITAS FISIK DI RUMAH SAKIT SURABAYA - Ernawati, Yayuk; Septianingrum, Yurike; Wijayanti, Lono; Soleha, Umdatus (Library Unit collaborates with the Institute for Research and Community Service, College of Health Sciences Husada Jombang, 2025)
Background: Stroke patients often experience hemiplegia or hemiparesis. Proper treatment can help the healing and recovery process. Objectives: This study aims to provide an overview of the implementation of the combination of Range of Motion (ROM) and Head of Bed (HOB) Elevation in ischemic stroke patients with impaired physical mobility in patient Mrs. L in Room Y, Surabaya Hospital. Methods: This type of research is descriptive, using a case study approach. Nursing care was provided from June 4 - June 6, 2025. The results of the assessment on Mrs. L had a stroke with hemiparesis. The nursing problems obtained were decreased intracranial adaptive capacity, impaired physical mobility, and risk of falling. The interventions given were head up 30 ⁰, Range of Motion, and education of patients falling. Results: The application of a combination of Range of Motion and Head of bed elevation with impaired physical mobility significantly helps the healing and recovery process in stroke infarction patients. Conclusion: Evaluation of nursing problems shows that the nursing diagnosis of decreased intracranial adaptive capacity and impaired physical mobility is partially resolved with increased muscle strength from 1 to 2 and increased range of motion, and the patient does not fall.